Perceived Leadership Styles and Commitment to Service Quality Among Academic Staff: The Mediating Influence of Job Satisfaction - Raemah, Abdullah Hashim (2010)
Past researches have suggested that some universities in Malaysia were losing student because their standard of service quality was not up to the expectation. This gives emphasis that there is some concern in the way the students' were being treated or handled. With the global and national competition, growth of public and private universities there is a need for academic leaders to not only transform the national academic outlook from the national perspective but also to motivate the academic staffs' commitment towards service quality excellence. Therefore, the primary objective of this study was to explore the relationships of perceived leadership styles and commitment to service quality, mediated by job satisfaction among the academic staff in selected Malaysian Universities. Specifically the objectives were : 1) to determine the status of commitment to service quality among the academic staff in selected Malaysian Universities; 2) to determine the status of job satisfaction among the academic staff in selected Malaysian Universities; 3) to determine the relationships of perceived leadership styles on the commitment of the academic staff towards service quality in selected Malaysian Universities; and 4) to determine the mediating effects of job satisfaction on the relationships of perceived leadership styles and the commitment of academic staff to service quality in selected Malaysian Universities. Based on the objectives and research questions, four (4) hypothesis were proposed to determine the relationship between perceived leadership styles and commitment to service quality and the mediating effects of job satisfaction on the relationship between perceived leadership styles and commitment to service quality of the academic staff. The sample for this study consisted of academic staff from six universities in the Klang Valley, Malaysia. Majority of the respondents were from the business faculty, between the ages of 30 and less than 40 years old, with masters and other qualifications and with between 1 and less than 5 years of teaching experience. The total useable questionnaires were 387 with a response rate of 36 percent from both private and public universities. This study reveals that perceived leadership styles have a significant positive relationships on the academic staffs commitment to service quality. Job satisfaction was found to have only a partial mediating effect on transformational and transactional leadership styles and commitment to service quality. There were also significant differences in academic staff commitment to service quality and job satisfaction among the public and private universities in Malaysia. The findings of this study contribute in the specific area of literature, theory and also in research design. Among the recommendations made to the policy makers and academic leaders at the universities were in enhancing the commitment of the academic staff to service quality by achieving job satisfaction, ranking service quality as the number one priority and opening avenues for collaboration with the government in training of academicians in leadership. Several suggestions were also made for future studies such as the inclusion of new variables, dyadic methods of sampling, longitudinal methods of data collection and the adaption of measurements to suit the local culture.